Understanding EFL preservice teachers’ intentions and concerns of integrating AI in their future ELT - I Putu Indra Kusuma; Sandrotua Bali; Ehsan Namaziandost; Luh Gd Rahayu Budiarta; Ming-Chou Liu; Made Hery Santosa (Universitas Syiah Kuala, 2026)
Research shows that English as a foreign language (EFL) in-service teachers are widely implementing AI in English language teaching (ELT). It remains unclear how novice pre-service teachers (PSTs) with limited teaching experience intend to integrate AI into ELT. At the same time, research addressing the concerns of PSTs is scarce. Nonetheless, they represent the forthcoming generation of teachers who will engage with AI in ELT. Given the above gaps, this study aimed to explore the intentions and concerns of EFL PSTs regarding the integration of AI in ELT. This research employed a basic qualitative approach and recruited EFL PSTs enrolled in an English teacher education program at a state university in Indonesia. The data was collected through an open-ended questionnaire and semi-structured interviews. Then, the data from the questionnaire was analyzed using the content analysis method, and the data from the interviews were analyzed using the inductive thematic analysis method. The open-ended questionnaire indicated that EFL PSTs demonstrated significant intentions to use AI. The interview findings also indicated an intention to integrate AI in future instructional design, alongside favorable perceptions of AI for teaching and its application by students in learning contexts. They also expressed both negative and constructive concerns regarding the integration of AI in ELT. Three new implications, such as one theoretical and two practical ones for EFL PSTs, teacher education programs, and policymakers, are drawn for English teacher education programs to enhance EFL PST preparation.